Macroscopic Pharmacognostical Identification and Authentication of Collected Specimens of Lekhaneeya Mahakashaya with Rasapanchaka Profiling and Therapeutic Insights in Arbuda - Kiran Paudel,; Krutika Chaudhary,; SudipKumar Rath, (Journal of Ayurveda Campus, 2025)
Introduction: Laghu (Light), Ushna (Hot), Tikshna (Sharp), Vishada (Clear), Rukshya (Dry), Sukshma (Minute), Khara (Rough) and Sara (Mobile) are the attributes of the Dravyas of Lekhaneeya Mahakashaya. These characteristics of Dravyas promote the depletion of Kapha Dosha, the stimulation of Agni (digestive enzymes), the absorbing of Dhatus (body tissues) and Malas (body excreta) and the Sushka (drying) of those undesirable Dhatus-Malas. Tridosha, Dhatu, Agni and Mala vitiation results in cancer (Arbuda). Therefore, because of its Ushna, Tikshna and Ruksha Guna of Lekhaneeya Dravya acts on the overgrowth of Dhatus (tissues) in the body by its Lekhana Karma.Materials and Methods: Plants were collected from Jaipur, India and Kritipur, Hetauda and Kathmadu, Nepal. Authentication of the Plants were done from KATH, Godawari, Nepal and Rajasthan University, Jaipur, Rajasthan, India. Several Ayurvedic and botanical textbooks were used to verify the Rasapanchaka of the plants.Results: The species of the Lekhaneeya Mahakashaya from India and Nepal were identified and collected for this study. Katu, Tikta Rasa, Ruksha, Tikshna, Laghu and Guna are primarily responsible for Lekhana Karma. Ushna Virya and Katu Vipaka allivate the Shoshana of the Kapha Dosha and Vata Doshas. Mandagni causes the vitiation of Kapha Dosha and the production of Ama on Rasa Dhatu. This results in Vitiated Dosha-Dhatus Vimargagamana and Srotorodha. This process causes an Arbuda (tumor) to emerge and primarily affects the Mamsa (muscular tissue). The Ushna, Tikshna and Ruksha Guna of Lekhaneeya Dravyas aid in stimulating all Agnis and reducing Kapha.Conclusion: Ruksha, Ushana and Tikshna Guna are predominant in all ten Lekhaneeya Dravya. Lekhaneeya Mahakashaya can be utilized to treat many forms of Arbuda (Cancer) because of these qualities.